Um mapeamento sistemático da literatura em melhoria do processo de software e medição de software por propostas de gamificação e jogos sérios - LIMA, João Luís dos Reis (2019)
Context: the use of serious games and gamification in software engineering is not so recent. However, recent technologies have provided new opportunities for their application in both the academic and industrial settings, and may increase the engagement of students and staff. Objective: the objective of this work is to identify different approaches in the teaching of Software Measurement and Software Process Improvement by gamification proposals and serious games through a systematic mapping study. Seeking to characterize the state of the art on the use of methods related to gamification and serious games in the mentioned subjects. Method: we performed a systematic mapping study to identify primary and secondary studies that address the use, proposal or evaluation of gamification, serious games, their elements and game mechanics in software engineering. Results: we identified 167 primary and secondary studies, published between 2001 and 2017. Preliminary studies show a close relationship between the methods used in the researched jobs, since in 92 serious games are used, whereas in 71, gamification is the method explored. Conclusions: although the use of serious games and gamification in software engineering is not recent, there is a large space to be explored, especially in Software Process Improvement and Software Measurement.